PHILOSOPHICAL ANALYSIS OF THE PROCESSES OF TRANSFORMATION OF THE PERSON INTO THE DIGITAL SOCIETY - Teshayeva Gulchehra Murodovna (Western European Studies, 2025)
This article covers the processes of transformation of an individual into a digital society, the reforms being carried out in our country, the issues of organizing distance learning in the education sector, and the reforms of the Digital Uzbekistan-2030 Strategy. The President's policy in the field of developing a digital society, government decisions and their implementation in practice are discussed. The practical significance of the reforms carried out in our country and their important aspects in improving the social life of the population are emphasized
Keywords: transformation; digital society; strategy